2016
DOI: 10.3389/fpsyg.2016.01962
|View full text |Cite
|
Sign up to set email alerts
|

Can Contraries Prompt Intuition in Insight Problem Solving?

Abstract: This paper aims to test whether the use of contraries can facilitate spatial problem solving. Specifically, we examined whether a training session which included explicit guidance on thinking in contraries would improve problem solving abilities. In our study, the participants in the experimental condition were exposed to a brief training session before being presented with seven visuo-spatial problems to solve. During training it was suggested that it would help them to find the solution to the problems if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 99 publications
2
27
0
Order By: Relevance
“…As a final consideration, we would like to focus on the major role of Violation of expectations which emerged in both studies. In a totally different context, i.e., a cognitive analysis of the reasoning mechanisms underlying problem solving and humor, it has been demonstrated that contrast is key to any exploration of alternative strategies in insight problem solving (Branchini et al, 2015 , 2016 ), as well as in inductive (Gale and Ball, 2012 ) and deductive thinking (Augustinova, 2008 ), and it has also been argued that contrast is fundamental to the incongruity mechanism in humor (Colston, 2002 ; Canestrari and Bianchi, 2012 , in press ; Canestrari et al, 2017 ; see reviews in Keith-Spiegel, 1972 ; Martin, 2007 ; Larkin-Galiñanes, 2017 ). The results discussed in the present paper (in particular with respect to the Violation of expectations) suggest that contrast also represents a link between insight problem solving and humor in terms of the cognitive emotions triggering pleasures of the mind.…”
Section: Discussionmentioning
confidence: 99%
“…As a final consideration, we would like to focus on the major role of Violation of expectations which emerged in both studies. In a totally different context, i.e., a cognitive analysis of the reasoning mechanisms underlying problem solving and humor, it has been demonstrated that contrast is key to any exploration of alternative strategies in insight problem solving (Branchini et al, 2015 , 2016 ), as well as in inductive (Gale and Ball, 2012 ) and deductive thinking (Augustinova, 2008 ), and it has also been argued that contrast is fundamental to the incongruity mechanism in humor (Colston, 2002 ; Canestrari and Bianchi, 2012 , in press ; Canestrari et al, 2017 ; see reviews in Keith-Spiegel, 1972 ; Martin, 2007 ; Larkin-Galiñanes, 2017 ). The results discussed in the present paper (in particular with respect to the Violation of expectations) suggest that contrast also represents a link between insight problem solving and humor in terms of the cognitive emotions triggering pleasures of the mind.…”
Section: Discussionmentioning
confidence: 99%
“…First, we applied Generalized Linear Mixed Models (GLMM), as implemented in the glmer functions in the lme4 package [69] within the R-software (Version 3.6.0, R Core Team, Wien, Austria) [70], to explore the salience of different content types, and the influence of class level (second, fourth-graders) and gender (males, females) on responses (objectives 1a, 1b, and 2b). We performed Mixed Model ANOVA Tables (Type 3 tests) via likelihood ratio tests implemented in the afex package of the R-software [71][72][73][74]; for applications see, for example, [32,[75][76][77][78][79][80][81]. For the various analyses, class level and gender were the between-subject factors; content types were the within-subject factors.…”
Section: Discussionmentioning
confidence: 99%
“…There was considerable diversity within the categories of procedures classified as "restructuring" and "divergence" in Table 1. For example, as well as the more traditional forms of instructional training (Ansburg & Dominowski, 2000;Cunningham & MacGregor, 2008) there were training procedures based on mindfulness (Ostafin & Kassman, 2012) and "thinking in opposites" (Brancini et al, 2016;Bianchi et al, 2019). Similarly, in addition to well-established methods for facilitating divergent thinking, the list included a test of "overinclusive thinking" (Chiu, 2015).…”
Section: Discussionmentioning
confidence: 99%